Clinical decision-making before discharge in hospitalized persons with schizophrenia: a Spanish Delphi expert consensus - Montes, José Manuel; Agüera-Ortiz, Luis; Mané, Anna; Martinez-Raga, Jose; Gutiérrez-Rojas, Luis (Frontiers in Psychiatry, 2024)
The care of people with schizophrenia (PWS) is usually provided in an outpatient setting by community mental health teams. However, PWS frequently require inpatient treatment because of a wide array of clinical, personal and/or social situations. Unfortunately, to our knowledge, there are no guidelines available to help psychiatrists in the decision-making process on hospital discharge for PWS. The aim of this project was to develop an expert consensus on discharge criteria for PWS after their stay in an acute inpatient psychiatric unit. Using a modified Delphi method a group of 42 psychiatrists throughout Spain evaluated four areas of interest regarding this issue: clinical symptomatology, treatment-related factors, follow-up health care units after discharge, and physical health and monitoring. After two rounds, among the 64 statements, a consensus was reached for 59 (92.2%) statements. In three (17.7%) of the 17 statements on 'clinical symptomatology' and 2 (13.3%) of the 15 statements on 'follow-up health care units after discharge', a consensus was not reached; in contrast, a consensus was reached for all statements concerning 'treatment-related factors' and those concerning 'physical health and monitoring'. The consensus results highlight the importance for discharge of the control of symptoms rather than their suppression during admission and of tolerability in the selection of an antipsychotic. Although there is a lack of relevant data for guiding the discharge of PWS after hospitalization in an acute inpatient psychiatric unit, we expect that this consensus based on expert opinion may help clinicians to make these decisions.